Optimization of the shear tool deployment system for removal of steel piled jackets. (May 2016) - Godjevac, Milinko; Huijsmans, R HM; van der Eijk, Hidde M; de Grave, Louis
It is estimated that there are more than 200 steel piled platform installations in the North Sea which have reached the end of their life and have to be cut and removed. In comparison with other cutting methods, the shear tool cutting method offers the greatest potential regarding optimizing the time of the operation. However, the existing shear tool is susceptible to blade bending–related failures caused by heave motions of the heavy lift vessel to which the tool is attached. While there are many studies related to the operability and workability of sea surface structures, this study focuses on the operability and workability of an underwater structure, the shear tool system. In order to improve the performance of the existing shear tool, the new shear tool system has been designed as an equalizer with additional counter weights; thus, this system acts as a passive heave compensator. In total, six different design concepts have been assessed using a multicriteria sensitivity analysis, and the most promising concept has been selected. Afterwards, the performance of the new design was compared with the performance of the existing tool by calculating their operability and workability for the removal of the benchmark (Northern North Sea jacket) structure. The workability calculation was based on 15 years of environmental conditions and results indicate that the new design leads to 50% workability increase.